2019
DOI: 10.1039/c9lc00608g
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterned biofunctional lubricant-infused surfaces promote selective localized cell adhesion and patterning

Abstract: Micropatterned lubricant-infused biofunctional surfaces exhibit biofunctionality and omniphobicity simultaneously which leads to targeted cell attachment and alignment, both in surfaces and in microfluidic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Recently, omniphobic coatings have been introduced on the surface of biomedical devices for reducing biofouling and the resultant blood coagulation, [ 20–29 ] while minimizing the administration of anticoagulants. [ 30 ] Liquid‐infused surfaces are one of the recent classes of omniphobic surfaces which have shown to significantly suppress biofouling and thrombosis with their performances surpassing previous anticoagulant based strategies in terms of longevity under blood flow and anti‐biofouling ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, omniphobic coatings have been introduced on the surface of biomedical devices for reducing biofouling and the resultant blood coagulation, [ 20–29 ] while minimizing the administration of anticoagulants. [ 30 ] Liquid‐infused surfaces are one of the recent classes of omniphobic surfaces which have shown to significantly suppress biofouling and thrombosis with their performances surpassing previous anticoagulant based strategies in terms of longevity under blood flow and anti‐biofouling ability.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 ] Liquid‐infused surfaces are one of the recent classes of omniphobic surfaces which have shown to significantly suppress biofouling and thrombosis with their performances surpassing previous anticoagulant based strategies in terms of longevity under blood flow and anti‐biofouling ability. [ 20–25,27–30 ] However, in order for these surfaces to sustain their omniphobic and repellent properties, the lubricant layer must be stable on the surfaces, making them difficult to use in open‐air applications where the lubricant is susceptible to evaporation. [ 31 ] Another class of omniphobic surfaces is those with structural modifications wherein the micro‐ and nano‐scale topography of the surface provides omniphobic properties.…”
Section: Introductionmentioning
confidence: 99%
“…113,161,162 Our group has shown that the combination of lubricant-infused surfaces with micropatterning strategies in microfluidics with glass substrates can result in the creation of localized bio-interfaces with high sensitivity in capturing secondary antibodies or cells. 163 Integration of this protocol with PDMS microfluidics can bring about flexible biosensors with significantly high sensitivity due to the presence of lubricant.…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…Furthermore, patterning of the biomolecules in PDMS microfluidic channels allows for multiplex detection of different biomarkers for high throughput applications. Incorporating simple methods such as microcontact printing via use of PDMS stamps with microfluidic fabrication 58,163 could significantly simplify the method compared to other patterning techniques such as non-contact printing with piezoelectric inkjet printing technology, 167 photolithographic patterning using a proper photomask, 168 and multifaceted tree-shape designs for the generation of 2 dimensional (2D) concentration gradients. 169 Benefiting from hydrodynamic resistances induced by channel geometries, an innovative, simple microfluidic design has also been demonstrated to generate 1D and 2D concentration gradients with a small footprint size, 117 which could potentially be used in PDMS microfluidic applications.…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…[ 31–33 ] Two key aspects that can be modified in ELISA‐IFA to further improve its performance and functionality are the proper immobilization of capture biomolecules and the use of optimal surface blocking agents to reduce the background noise often associated with fluorescence‐based assays. [ 45–47 ] For immobilization of biorecognition elements, contact printing and noncontact printing strategies have been widely used to generate microarrays of biorecognition elements (e.g., antibodies) using desired chemical linkers (e.g., amine or carboxyl groups). [ 48–50 ] The microarrays shape, diameter, thickness, homogeneity, and binding mechanism are important attributes to evaluate the efficacy of different microarray biosensing surface strategies.…”
Section: Introductionmentioning
confidence: 99%